What is Driving Public Transport in Perth: Understanding Determinants and Dynamics? - Nau, S. Zaung (2017)
The main objective of this paper is to systematically examine primary determinants that explain both spatial and temporal variations in public transportation use in Perth. It is also to offer a comprehensive and rigorous analysis of use-determinants and develops a robust predictive model based on land use characteristics, urban form, socioeconomic conditions and public transport availability factors which can inform policymaking. It employs the data on revealed preferences derived from smart cards to analyse the variations in temporal and spatial patterns of public transport use in Perth depending on types of patrons, the origin suburbs of their journeys and the day and time of travel. The research deploys factor analysis to identify latent variables among a broad range of explanatory variables and then applies the multiple regression analysis to develop a predictive model of public transport use in Perth metropolitan suburbs. The main finding from this research is that the Bus/Ferry service provision density is the most important factor in explaining the spatial and temporal variations in public transport use in Perth’s metropolitan suburbs, along with income factor and land use characteristic (resident and student population density). It also has a practical implication for public transit planning for Perth to increase public transport usage and promote the role of public transit in Perth. Therefore, this paper points out the importance of addressing the combined influences of land use characteristics, socioeconomic factors, and service provision factors in shaping public transport use.